2003
DOI: 10.1124/jpet.103.059139
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Human Organic Anion Transporters with Diuretics

Abstract: The tubular secretion of diuretics in the proximal tubule has been shown to be critical for the action of drugs. To elucidate the molecular mechanisms for the tubular excretion of diuretics, we have elucidated the interactions of human organic anion transporters (hOATs) with diuretics using cells stably expressing hOATs. Diuretics tested were thiazides, including chlorothiazide, cyclothiazide, hydrochlorothiazide, and trichlormethiazide; loop diuretics, including bumetanide, ethacrynic acid, and furosemide; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
110
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 25 publications
(37 reference statements)
12
110
3
6
Order By: Relevance
“…Furosemide and bendroflumethiazide inhibited tracer uptake with IC 50 values for mOat1 of 8 Ϯ 1 and 8 Ϯ 3 M, respectively (Fig. 1A), which were comparable with previously reported K i values for rat and human OAT1 (13,36). The IC 50 values for furosemide and bendroflumethiazide in mOat3 were 2.8 Ϯ 0.1 and 21 Ϯ 3 M, respectively (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Furosemide and bendroflumethiazide inhibited tracer uptake with IC 50 values for mOat1 of 8 Ϯ 1 and 8 Ϯ 3 M, respectively (Fig. 1A), which were comparable with previously reported K i values for rat and human OAT1 (13,36). The IC 50 values for furosemide and bendroflumethiazide in mOat3 were 2.8 Ϯ 0.1 and 21 Ϯ 3 M, respectively (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The IC 50 values for furosemide and bendroflumethiazide in mOat3 were 2.8 Ϯ 0.1 and 21 Ϯ 3 M, respectively (Fig. 1B), also comparable with values previously obtained for human OAT3 in one prior study (13). Thus both furosemide and bendroflumethiazide inhibited tracer uptake by mOat1 and mOat3 in a concentration-dependent manner, consistent with their being substrates for these transporters.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Organic anion transporter 1 (OAT1/SLC22A6) and OAT3 (SLC22A8) have broad substrate specificities, and kinetic analyses using rat kidney slices have suggested that Oat1 mainly is responsible for the renal uptake of hydrophilic and small organic anions, whereas Oat3 is responsible for the uptake of more bulky organic anions (8 -10). Diuretics interact with OAT1 and OAT3, and, particularly, loop diuretics such as furosemide and bumetanide are substrates of OAT (11,12). Recently, Oat1 knockout mice were generated, and it was demonstrated that Oat1 was responsible for the renal uptake and pharmacologic action of furosemide (13).…”
mentioning
confidence: 99%
“…[10][11][12] Loop and thiazide diuretics must first be secreted by renal proximal tubule cells before reaching their sites of action on the apical membrane. [13][14][15][16] Interactions between diuretics and other secreted drugs, including antibiotics, NSAIDs, antivirals, as well as organic acid in the setting of renal failure, can limit their secretion and natriuretic effects. Kir4.1/5.1 inhibitors that act directly on the basolateral membrane should circumvent this limitation.…”
mentioning
confidence: 99%